Сучасні реалії споживання плодово–ягідної продукції на півдні України - Колокольчикова, Ірина Володимирівна; Колокольчикова, Ирина Владимировна; Kolokolchykova, Iryna (My University, 2019)
UK: У статті розглянуто сучасні реалії споживання плодово-ягідної продукції на Півдні України. Загальна тенденція споживання свідчить про низькі показники в областях Півдня України, які нижчі за середній показник у країні. Встановлено, що серед чотирьох областей регіону найкращі показники виробництва та споживання плодово-ягідної продукції – в Одеській області. Визначено вплив таких економічних чинників, як ціна та рівень доходів на душу населення, на купівельну спроможність українців. Проаналізовано динаміку цін на плоди та інші продукти харчування споживчого кошику, рівень доходів покупців. Узагальнюючим висновком є те, що на рівень споживання продукції галузі садівництва впливає не тільки рівень цін на самі плоди та ягоди, а й ціна на інші важливі для пересічних громадян продукти (картоплю, молоко та м'ясо), які є у споживчому кошику покупця. Результатом низького рівня купівельної спроможності та рівня споживання плодів та ягід є вибірковий підхід до купівлі фруктів, економія витрат на користь інших продуктів харчування. RU: В статье рассмотрены современные реалии потребления плодово-ягодной продукции на Юге Украины. Общая тенденция потребления свидетельствует о низких показателях в областях Юга Украины, кото- рые ниже среднего показателя в стране. Установлено, что среди четырех областей региона лучшие показатели производства и потребления плодово-ягодной продукции в Одесской области. Определено влияние таких экономических факторов, как цена и уровень доходов на душу населения, на покупательную способность украинцев. Проанализирована динамика цен на плоды и другие продукты питания потребительской корзины, уровень доходов покупателей. Обобщающим выводом является то, что на уровень потребления продукции отрасли садоводства влияет не только уровень цен на сами плоды и ягоды, а и цена на другие важные для рядовых граждан продукты (картофель, молоко и мясо), которые есть в потребительской корзине покупателя. Результатом низкого уровня покупательной способности и уровня потребления плодов и ягод является избирательный подход к покупке фруктов, экономия затрат в пользу других продуктов питания. EN: The article deals with the modern realities of consumption of fruit and berry products in the South of Ukraine. The General trend of consumption indicates low rates in the regions of Southern Ukraine, which are below the average in the country. It is established that among the four regions of the region the best indicators of production and consumption of fruit and berry products in the Odessa region. The minimum production volumes are in the Nikolayev region. In the whole region among fruits preference is given to the production of apples, cherries, cherries and apricots. Grapes are the hallmark of Odessa region. The balance of consumption of the industry's products reveals the volume of receipt and use of fruits and berries. The main channels of use is the implementation in all directions and processing. The greatest losses of a crop at use of production were observed in the Zaporozhe and Kherson region. The influence of such economic factors as price and per capita income on the purchasing power of Ukrainians is determined. It is established that over the past five years, the prices of fruits and berries have grown rapidly, honor three times. Along with the prices for fruits, prices for such basic food products of Ukrainians as meat, milk and potatoes have also increased. This is a negative trend, because it affects the amount of fruit that the Ukrainian population buys. The income of the population over the past three years has increased by only a quarter. This is a very slow growth, which does not increase the cost of buying food, including fruits. In the reporting year, the highest rates of income per person in Zaporizhzhya and Odessa region. The lowest income in the Kherson region. In the Kherson region there is generally the lowest rate of consumption of fruits and berries and the lowest income of the population. A generalizing conclusion is that the level of consumption of horticultural products is influenced not only by the level of prices for fruits and berries themselves, but also by the price of other important products for ordinary citizens (potatoes, milk and meat) that are in the consumer basket of the buyer. The result of the low level of purchasing power and consumption of fruits and berries is a selective approach to the purchase of fruits, saving costs in favor of other foods.
Modern realities of consumption of fruits and berries in southern Ukraine
Keywords: ринок; купівельна спроможність; норми споживання; ціна; дохід; платоспроможність; споживчий кошик; рынок; покупательная способность; нормы потребления; цена; доход; платежеспособность; потребительская корзина; market; purchasing power; consumption rates; price; income; solvency; consumer basket